Cascaded membrane and chromatography technologies for fractionating and purifying of bovine milk oligosaccharides. (September 2022) - Yang, Baoyu; Zhang, Minghui; Qiao, Weicang; Zhao, Junying; Chen, Jingyao; Yang, Kai; Hu, Jufeng; Hou, Juncai; Chen, Lijun
Abstract: We previously reported that major bovine milk oligosaccharides (BMO) can qualitatively and quantitatively analyzed using ultra high liquid chromatography on a high sensitivity fluorescence detection instrument; the method does not require the removal of lactose and uses small (only 100 μL) samples. In this study, we extended our strategy to fractionation and purification of BMO using membrane separation and chromatography techniques. The effects of membrane molecular weight cut-off (MWCO) and diafiltration the efficiency of the overall process were evaluated, with process optimization leading to suitable MWCOs for microfiltration (ceramic, 0.1 μm), ultrafiltration (spiral wound organic membrane, 30 kDa), and nanofiltration (spiral wound organic membrane, 500–700 Da). Total BMO recoveries of 97.36, 95.58, and 98.30% were observed for the microfiltration, ultrafiltration, and nanofiltration stages, respectively, with corresponding membrane fluxes of 75.74, 76.90, and 81.68 L/(m 2 ·h), respectively. In addition, the crude BMOs were further purified using size-exclusion chromatography, activated charcoal, lactase digestion, dialysis, crystallization, and anion-exchange chromatography. Anion-exchange chromatography with Q Sepharose Fast Flow anion-exchange resin was found to be more suited to industrial BMO production than other methods; it not only effectively separates lactose and oligosaccharides, but also exhibits dynamic adsorption capacity of 1.20 mg BMOs /mL gel . Graphical abstract: Image 1 Highlights: Crude bovine milk Oligosaccharides (BMO) were successfully enriched by integrated membrane technology. Low molecular weight lactose and BMO cannot be effectively separated by nanofiltration. Q sepharose fast flow anion exchange resin is most suitable for further industrial purification of BMO.